Pengaruh Pembiayaan Mudharabah, Musyarakah dan Ijarah Terhadap Profitabilitas (ROA) Pada Bank Umum Syariah di Indonesia - Novita Restu Widanti; Wirman Wirman (Jurnal Ilmiah Ekonomi Islam, 2022)
This study aims to determine the effect of partial and simultaneous mudharabah, musyarakah, and ijarah financing on the profitability (ROA) of Islamic commercial banks in Indonesia. This study uses quantitative methods. The data taken in this study are secondary data and time series obtained from the Otoritas Jasa Keuangan (OJK). The sample uses the 2016-2020 quarterly financial statements. The data of this study were processed by multiple linear regression analysis, classical assumption test, and hypothesis testing using IBM SPSS version 25. The results of this study indicate that: (a) Mudharabah has a positive effect on profitability (ROA) (b) Musyarakah has no effect on profitability (ROA) ) (c) Ijarah has a negative effect on profitability (ROA) (d) Mudharabah, Musyarakah, and Ijarah have a significant effect on profitability (ROA).